Observations on the Age and Growth of Shank (Acanthopagrus latus (Houttuyn, 1782)) from Al-Razzazah Lake - Dauod, H.A.M.; Al-Aamery, R. A.; Ali, A. I.; Chabuk, F. M.; Abbas, K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
) were taken from three stations at Al-Razzazah lake,by using a range of gill nets and seine nets. A total of 318 fish were taken from all stations. The age data determined from the scales showed that there were eight age classes present in station 1 and 2 and seven age classes in station 3. The increment in length of A. latus at the area of study showed a tendency to decrease with the increase in age after the fourth year of life.  The length- weight relationships of both sexes specimens are expressed by the following equations: Log ï· = -1.93 + 2.67 Log ï¬â€¦.. for station (1) fish Log ï·= -2.08 + 2.74 Log  ï¬ â€¦. For station (2) fish Log ï·= -2.02 + 2.39 Log ï¬ â€¦. For station (3) fish  It seems from the above equations that the growth of A. latus in the area of study is allometric.